The epidemiology of facial trauma in a city in Northern Brazil (Research, Society and Development, 2021)
The aim of the present work is to carry out an epidemiological study with patients with facial fractures who were operated on in the city of Belém do Pará.  In the Years 2015 to 2020, in addition to a literature search on the topic, data was collected on the system of a health insurance company in the city of Belém. It was approved by the Research Ethics Committee of the Dental Research Center and São Leopoldo Mandic Dental School. Facial fractures in Belém do Pará had a 3.5 times higher incidence in men than women. One of the explanations lies in the increased number of men involved in interpersonal aggression, violent sports and traffic accidents. Mostly there were fractures in the zygomatic area and in the nose. The vast majority were treated with open reduction. Facial fractures are multifactorial, but traffic awareness campaigns and alcohol abuse should be incorporated into government projects in each national area.